Pneumatic Breakwaters and Their Use for Ships protection in Coastal and Offshore Areas of Persian Gulf - Milad Bamdadinejad; Mohammad Javad Ketabdari; Saman Rezaei (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
Pneumatic breakwater is a kind of wave energy damping structure which is capable of reducing a portion of wave energy. The structure utilizes an air bubble column deep in water to induce a counter flow which opposes the wave current resulting in damping of its energy and the height of the wave. Fast installation with the least space occupied along with posing no obstacle for shipping and maneuvering are advantages of this structures. Although the disadvantage of this method can be wasting of almost half the energy of outgoing air. Using this method, a range of waves with lower height can be achieved. To draw the most advantage out of this method, the pneumatic breakwater can be combined with Floating breakwater. In order to explore the effectiveness of Hybrid breakwater, a physical or numerical model in deeper water depth is required. Utilizing this method in coasts where other kind of ordinary breakwaters are not practical and temporarily in the vicinity of shore in deeper water is economically effective. This breakwater can be attached to the ship (DAHET) or rig (ATAB). Hybrid system creates a safe atmosphere for smooth transfer of the passengers of crew boats to and from wharf in a continuous manner even in rough sea and bad weather condition. Case study in Persian Gulf indicates that pneumatic breakwater is practical in Persian Gulf except for longitude between 51° and 57° and latitude between 24° and 28° Northern which extends from eastern north to 14 Kilometers of Parsian Coasts and 30 Kilometers of Lengeh Port and from western south to 6 Kilometers of Dubai coasts to Abuzabi and from eastern north to 12 km of Kargan port to Sirik and from western south to 130 Kilometers of eastern coasts of Qatar.